Opportunities and prospects of the Economic belt of the Silk way - Омарова, М А.; Арзыкулов, А. А. (Journal of Oriental Studies, 2018)
In article authors consider the possibilities and the prospects of strategy «An economic belt of the Silk way» which has been begun within an initiative «One belt – one way». As this initiative has been offered the People’s Republic of China, the share of China in this project undoubtedly big, and in process of realization will grow. In four years since the beginning of the project enormous work has been performed: the legal-contractual basis is created, there were financial institutions, etc. And Kazakhstan on the geographical arrangement has very advantageous geostrategic position, and it is necessary to use it. In the conditions of world integration all participants of this project will be the winner.